The transition of municipal consulting and diagnostic centers to new financial and economic mechanisms through the application of the principles of public - private partnership is a requirement of time - Kravchenko, V. V. (Journal of Education, Health and Sport, 2017)
Introduction. Extremely acute problem of the national health system is under funding industry as a whole, as a system of medical care and secondary outpatient care in particular. This situation requires an immediate solution by finding new financial and economic mechanisms and attracting additional ones and more effective funding sources, which necessitates the transition to its innovative model of development through the use of mechanisms of public-private partnerships, which provide structural and financial industry efficiency. Purpose. To substantiate the necessity of transition of communal consulting and diagnostic centers on new financial and economic mechanisms of governance through the application of the principles of public-private partnership. Materials and methods. The research was performed on the basis of the system approach and system analysis using the information - analytical method. The information base for their formation was the scientific work of foreign and domestic specialists in the organization and management of health care and the results of their own research. Results. According to the results of the study, it was found that, given the limited financial capacity of the state budgets of all levels, the development of state and communal outpatient clinics (consultative diagnostic centers) (KDC) is impossible without the introduction of new organizational forms of activity, financial and economic opportunities of private business. Conceptually new priority directions of work of consulting and diagnostic centers are offered. Conclusions. The article substantiates the necessity of transition of the KDC to new forms of management with the attraction of private capital through the use of public-private partnership mechanisms (PPP) Keywords: budget, public-private partnership, consulting and diagnostic center.